Predictors of Clinical Benefit with Intra-articular Hyaluronic Acid in Patients with Knee Osteoarthritis - A Narrative Review - Chevalier, Xavier; Sheehan, Brendan (Current Rheumatology Reviews, 2024)
Background: There is conflicting evidence regarding the efficacy of viscosupplementation with intra-articular hyaluronic acid injections in knee osteoarthritis. One possible explanation for the inconsistent findings on its efficacy is that only certain subpopulations of patients benefit from this therapy. Objective: The purpose of this narrative review is to succinctly summarize the existing data on the predictive factors of clinical response to intra-articular hyaluronic acid to identify the patient profile most likely to benefit from this therapy. Methods: For this narrative review, a PubMed search was conducted in January 2023, with no date limits, to identify publications reporting predictive factors of response to viscosupplementation using the following terms: hyaluronic acid OR viscosupplem* AND osteoarthritis AND knee AND predict*. Searches were limited to randomized controlled trials, systematic reviews and meta- analyses, or observational studies written in English. Other relevant references were identified by searching the references of retrieved articles. Results: The disease severity was found to reliably predict response to intra-articular hyaluronic acid injections; patients with less severe disease consistently had a more robust therapeutic response than those with more severe disease. Other clinical variables such as level of baseline pain did not reliably predict response. Body mass index, and possibly age, may also be independent predictors of the response. Conclusion: A review of the existing literature suggests that patients with less severe clinical symptoms and radiological findings, who are younger, and with a lower or normal body mass index are the best candidates for intra-articular hyaluronic acid therapy.
Keywords: disease severity